Green banking, green investment, and sustainability development banking in Indonesia - Alya Asyura; Ramadania Ramadania; Wendy Wendy; Mustarudin Mustarudin; Anggraini Syahputri (International Journal of Applied Finance and Business Studies, 2023)
Sustainability development was the primary imperative to protect the planet from damage. Sustainabilty development transformed business practices into environmentally responsible initiatives within the community, focusing on green projects and operations with sustainability at the forefront. This research analyzed the influence of green banking and green investment on firm value with profitability as an intervening variable. The research population was the banking sector listed on the Indonesian Stock Exchange in 2018-2022. Data analysis is performed using double regression with estimated data panel fixed effect model and sobel test. The research results indicate that green banking significantly and negatively affects profitability, while green investment has an insignificant and negative impact. However, both green banking and profitability have a positive and statistically significant influence on firm value. Green investment has a negative and insignificant effect on firm value. Lastly, profitability does not intervening the relationship between green banking and green investment on firm value.